2005
DOI: 10.1136/ard.2004.022277
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of sensory denervation in inflammatory arthritis (evidence of regulatory neuroimmune pathways in the arthritic joint)

Abstract: Objective: To investigate the direct effect of joint innervation on immune mediated joint inflammation in a patient with psoriatic arthritis (PsA). Case report: The patient developed arthritis mutilans in all digits of both hands with the exception of the left 4th finger, which had prior sensory denervation following traumatic nerve dissection. Plain radiography, ultrasonography and nerve conduction studies of the hands confirmed the absence of articular disease and sensory innervation in the left 4th digit. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 6 publications
0
30
0
1
Order By: Relevance
“…Thus, in human acute and chronic arthropathies, the elevated levels of synovial fluid EAA (31, 32) from damaged cellular tissue and EAA shown experimentally to be derived from the nerve terminals (25) could activate glutamate receptors expressed locally on synoviocytes to enhance cellular activation, inflammation, and pain states. Diminution of joint edema and allodynic behaviors by 50% or more with glutamate receptor blockade in the spinal cord, afferent nerve lesion, or intra-articular glutamate antagonists provides support for the role of neurotransmitter glutamate release in significantly impacting inflammatory events occurring in the joint (19,23,37,44,49).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Thus, in human acute and chronic arthropathies, the elevated levels of synovial fluid EAA (31, 32) from damaged cellular tissue and EAA shown experimentally to be derived from the nerve terminals (25) could activate glutamate receptors expressed locally on synoviocytes to enhance cellular activation, inflammation, and pain states. Diminution of joint edema and allodynic behaviors by 50% or more with glutamate receptor blockade in the spinal cord, afferent nerve lesion, or intra-articular glutamate antagonists provides support for the role of neurotransmitter glutamate release in significantly impacting inflammatory events occurring in the joint (19,23,37,44,49).…”
Section: Discussionmentioning
confidence: 94%
“…In subsequent studies, data were provided showing that 1) peripheral tissue damage releases glutamate and other neurotransmitter amino acids in the spinal cord, 2) dorsal horn sensitization mechanisms ensue, creating reverse sensory nerve firing directed toward the periphery, 3) neurotransmitter substances are release into the periphery, and 4) enhanced peripheral inflammation and nociceptive responses interpreted as pain continue in a vicious feedforward cycle (3, 22, 25, 31, 32, 36 -38, 40, 43-54, 57-59, 61-63). In fact, it has been shown that joint inflammation is significantly reduced in experimental arthritis and in patients with cut peripheral nerves (19,44). Lidocaine injected into the joint to block nerve transmission also reduces glutamate release in the joint (23).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These results suggest that substance P and GRP are involved together with cytokines in the neuroimmunomodulation that occurs in arthritic joints. It has been suggested that regulatory neuroimmune pathways in the joints are important mechanisms modulating the expression of arthritis [35]. Conversely, it has been reported that substance P and CGRP can stimulate the production of IL-1, IL-6, and TNF-a from various immune cells [33] [36][37][38].…”
Section: Discussionmentioning
confidence: 99%